Theory Adoption of Integrated Cattle and Oil Palm Farming System - Abd Rahman Ahmad; Aini Syafiqah Mohd Nasir; Hairul Rizad Md Sapry; Alaa S. Jameel (Communications of International Proceedings, 2022)
The increasing pressure on land, as well as the growing demand for livestock products, makes it increasingly important to ensure effective use of feed resources in the beef industry. There was lack of participation among farmers who are willing to adopt integrated cattle and oil palm farming system (ICOFS). Some of the farmers claimed that ICOFS could give negative impact on oil palm production such as damaging the immature oil palm, causing soil compaction and spread of genoderma fungi. The purpose of this paper is to review the theory related to ICOFS. Here, the factors affecting the adoption of ICOFS and constraints to the adoption of ICOFS were also discussed
Keywords: Integrated Cattle and Oil Palm Farming System; Household Production Theory; Theory on Adoption of Agricultural Technology